2015
DOI: 10.1021/acs.jpcb.5b02522
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Ion-Dependent Motion of Self-Propelled Droplets Due to the Marangoni Effect

Abstract: Chemically driven self-propulsion of soft matter is useful for various applications because it can move toward a desired location, without external power fields, in response to chemical signals in environmental media. We have developed a suitable steering mechanism to maintain the orientation of self-propelled droplets loaded with surfactant in fluidic environments. A spatial gradient of alkaline-earth metal ions induces directional sensing. These metal ions can be arranged in descending order of directional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…demonstrated that droplets emitting surface‐active chemicals are self‐propelled to seek a source of acid placed at one exit of a maze, finding the shortest path through the maze . In addition to these examples, self‐driven movements in response to various external fields, such as an electric field, an optical field, or a concentration gradient of metal ions, have been reported. These results are attributed to the characteristics of soft matter samples, such as their viscoelasticity, utilizing the kinetic energy created from the direct chemical gradient or gradients caused by physical fields.…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations
“…demonstrated that droplets emitting surface‐active chemicals are self‐propelled to seek a source of acid placed at one exit of a maze, finding the shortest path through the maze . In addition to these examples, self‐driven movements in response to various external fields, such as an electric field, an optical field, or a concentration gradient of metal ions, have been reported. These results are attributed to the characteristics of soft matter samples, such as their viscoelasticity, utilizing the kinetic energy created from the direct chemical gradient or gradients caused by physical fields.…”
Section: Figurementioning
confidence: 98%
“…Such movements of mesoscaled molecular assemblies have drawn attention, not only because of their characteristic nonlinear dynamics but also from the viewpoint of substance transport in a restricted space. Typical examples are directed movements of oil droplets on a surfactant‐coated substrate or at an air–water interface . For example, a nitrobenzene droplet containing iodine moves spontaneously on a glass surface coated with surfactants, absorbing the surfactants in front of the droplet .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[170] Here, we will give some examples of artificial self-propelled objects that could "sense" their environmental physicochemical conditions. [175][176][177][178][179][180] As elf-propelled dropletd riven by the Marangonif low (section 2.2.3) can also response to an external gradiento fp H, [177] rare earth metal concentration, [178,179] surfactant concentration, [180] or light intensity. The object can spontaneously move even though its environment is homogeneous, in which its movingd irection is random.…”
Section: Transporter-capture and Release Of Targetm Oleculesmentioning
confidence: 99%
“…The spontaneous motion of self-propelled droplets has recently attracted considerable attention in relation to energy transduction by living organisms, i.e., chemo-mechanical energy transduction. [1][2][3][4][5][6][7][8] Various kinds of droplet motion driven by a gradient in interfacial tension have been reported, as well as the propelled motion caused by diffusiophoresis. 9,10 In a related system, an oilwater system composed of an organic phase with potassium iodide and iodine and an aqueous phase containing stearyltrimethylammonium chloride (STAC) exhibits self-agitation at the oil-water interface, accompanied by spatio-temporal nonequilibrium fluctuation of the interfacial tension.…”
mentioning
confidence: 99%